Peran Intellectual Capital dan Profitabilitas terhadap Nilai Perusahaan - Ishak, Jouzar Farouq; Irawan, Arry; Tripuspitorini, Fifi Afiyanti; Hutapea, Riauli Susilawaty; Dahtiah, Neneng; Rufaedah, Yanti (Indonesian Accounting Literacy Journal, 2025)
In 2015, countries around the world adopted 17 goals with 169 fundamental targets to address issues affecting the world. The Sustainable Development Goals (SDGs) are a global commitment to improve the welfare of people for a better life. Each of the 17 SDGs has specific targets that need to be achieved by 2030 with everyone needing to do their part such as governments, individuals, and the private sector in this case industry. This study aims to determine the role of intellectual capital and profitability on firm value. The study sample consists of companies listed on Index Lq-45 on the Indonesia Stock Exchange from 2018 to 2024 using purposive sampling technique. This study employs a quantitative method. The data used in this study are secondary data obtained from financial reports published by the Indonesia Stock Exchange as well as annual reports published on company website. Hypotheses are tested using multiple linear regression analysis. The result show that, partially, intellectual capital has a significant negative effect on firm value, while profitability has a significant positive effect on firm value. Simultaneously, all variables have a significant positive effect on firm value.